A Prospective 2-Year Clinical Evaluation of Augmented Hip Abductor Tendon Repair. Issue 1 (22nd January 2020) - Ebert, Jay R.; Brogan, Kit; Janes, Gregory C.
Background: Hip abductor tendon (HAT) tearing is commonly implicated in greater trochanteric pain syndrome. Studies reporting surgical outcomes are often on small cohorts and with limited information on functional improvement. Purpose: To report the 2-year clinical and functional outcomes in a series of patients undergoing HAT repair augmented with a ligament augmentation and reconstruction system (LARS) ligament. Study Design: Case series; Level of evidence, 4. Methods: Between October 2012 and December 2016, a total of 142 patients with symptomatic HAT tears underwent open bursectomy, V-Y lengthening, and reattachment of the tendon with suture anchors augmented with a LARS ligament. This included 132 women (93%) with a mean age of 64.3 years (range, 43-84 years), a mean body mass index of 28.2 kg/m 2 (range, 20.0-41.3 kg/m 2 ), and an average duration of symptoms of 4.0 years (range, 6 months-20 years). Following surgery, patients underwent a graduated rehabilitation program consisting of hydrotherapy and land-based exercises. Patient-reported outcome measures (PROMs) were evaluated preoperatively and at 3, 6, 12, and 24 months postoperatively with the Harris Hip Score, Oxford Hip Score, 12-item Short Form Health Survey, and visual analog scale (VAS) for pain. Hip range of motion, hip abduction strength, 30-s single-leg stance (SLS), and 6-minute walk test (6MWT) capacity were evaluated. Patient satisfaction and perceived global rating of change were evaluated postsurgery. Analysis of variance was employed to evaluate clinical improvement over time. Results: A significant improvement ( P < .05) was demonstrated up to 24 months in all PROMs and clinical scores, including hip range of motion in all planes, hip abductor strength limb symmetry indices (mean ± SD; presurgery, 90.1% ± 42.5%; 24 months, 102.6% ± 15.0%), and the 6MWT (presurgery, 421.8 ± 91.9 m; 24 months, 509.7 ± 105.1 m). Furthermore, several variables, including pain (VAS and pain scores during the 6MWT and 30-s SLS) and patient-perceived improvement (global rating of change), continued to improve from 12 to 24 months. At 24 months, 95.7% of patients were satisfied with their surgical outcome (excluding 3 patients who underwent reoperation within the 24-month period). There was a 5.6% (n = 8) failure rate over the study period. Conclusion: HAT repair augmented with a synthetic ligament demonstrated significantly improved clinical and functional outcomes, high levels of patient satisfaction, and a relatively low failure rate up to 24 months postsurgery. Registration: ACTRN12616001655437 (Australian New Zealand Clinical Trials Registry).